Prognostic variables in high‐risk cutaneous squamous cell carcinoma: a review. (12th August 2016) - Cheng, Judy; Yan, Shaofeng
Abstract : Cutaneous squamous cell carcinoma (SCC) is a growing public health problem in the United States. A subset of high‐risk SCC exhibits a more aggressive clinical trajectory including increased local recurrence and lymph node metastasis. However, there are no universally accepted criteria to help define and manage these patients. This review provides an overview of the high‐risk features of cutaneous SCC, prognostic stratification of various staging systems and treatment options. It further examines the prognostic factors influencing the staging of cutaneous head and neck SCC.